A multi-technique approach to unveil the redox behaviour and potentiality of homoleptic CuI complexes based on substituted bipyridine ligands in oxygenation reactions. Issue 38 (29th July 2022) - Centrella, Barbara; Deplano, Gabriele; Damin, Alessandro; Signorile, Matteo; Tortora, Mariagrazia; Barolo, Claudia; Bonomo, Matteo; Bordiga, Silvia
Abstract : The reaction of Cu I (bpy)2 complexes with tBuOOH was followed by a multi-technique approach (DFT-supported lab-scale or synchrotron spectroscopies and electrochemistry). The findings evidence the formation of a Cu II OH species as reactive intermediate. Abstract : The effect of differently substituted 2, 2′-bipyridine ligands ( i.e. 6, 6′-dimethyl-2, 2′-bipyridine, 5, 5′-dimethyl-2, 2′-bipyridine, 6, 6′-dimethoxy-2, 2′-bipyridine and 2, 2′-bipyridine) on the reversible oxidation of the resulting Cu I homoleptic complexes is investigated by means of a multi-technique approach (electronic and vibrational spectroscopies, DFT, electrochemistry). Among the four tested complexes, [Cu I (6, 6′-dimethyl-2, 2′-bipyridine)2 ] (PF6 ) shows a peculiar behavior when oxidized with an organic peroxide ( i.e. tert -butyl hydroperoxide, t BuOOH). The simultaneous use of UV-Vis-NIR and Raman spectroscopy methods and cyclovoltammetry, supported by DFT based calculations, allowed identifying (i) the change in the oxidation state of the copper ion and (ii) some peculiar modification in the local structure of the metal leading to the formation of a [Cu II OH] + species. The latter, being able to oxidize a model molecule ( i.e. cyclohexene) and showing the restoration of the original Cu I complex and the formation of cyclohexanone, confirms the potential of these simple homoleptic Cu I complexes as model catalysts for partial oxygenation reactions.